ASPEK-ASPEK YANG MEMPENGARUHI JUMLAH KUNJUNGAN WISATA PANTAI PANGAH GANDAPURA - Usratul Maulini; Devi Andriyani (LPPM UNIMAL, 2021)
This study aims to analyze the factors that influence the number of tourist visits at Pangah Gandapura Beach. The data used in this study are primary data sourced from 100 respondents. The data analysis method used is multiple linear regression analysis. The results of the study partially travel distance, travel costs and age have a negative and significant effect on the number of Pangah beach tourism visits, income have a positive and significant effect on the number of Pangah beach tourism visits. Simultaneously trip distance, travel costs, age and income have a positive and significant effect on the number of Pangah Beach tourism visits.